Distribution Patterns of Mast Cells on Skipjack (Katsuwonus Pelamis) Infested with Endoparasitic Worms as Triggers for Anaphylactic Reactions - Dewi Farah Diba; Buana Basir (Faculty of Agriculture Musamus University, 2020)
This study aims to examine the pattern of mast cell distribution in the intestinal tract of skipjack fish (Katsuwono pelamis) infested with endoparasitic worms and prove the correlation between endoparasitic worms and mast cells which are always involved in hypersensitivity responses. The study was conducted in May to July 2018 at the Paotere Fish Auction Place and at the Animal Climatology Histology Laboratory of Hasanuddin University. A total of 30 skipjack fish originating from the Paotere TPI were used as research samples, the fish were then dissected to be taken inside the organs infested with endoparasitic worms and then fixed and made histopatalogis slide preparations with microtechnic procedures and hematoxylin-eosin staining to be observed under a microscope. The results showed that infestation of endoparasitic worms in the body of skipjack fish could grasp the active mast cells. Mast cells are distributed only to the gonads, gills and heart of skipjack fish (Katsuwonus pelamis).